Listen to Your Heart–Ecological Momentary Assessment of Interoceptive Accuracy, Awareness and Sensibility: A Pilot Study - Höller, Inken (Int J Environ Res Public Health, 2021)
Background: Interoception is a multi-facetted phenomenon including interoceptive accuracy, awareness and sensibility. Deficits in interoception have been associated with psychological distress. However, little is known about the course of interoception over time. The present study aimed at examining interoception in an ecological momentary assessment (EMA)-setting. Methods: A seven-day smartphone-based EMA was conducted in a community sample of sixty-one participants (age: M = 24.1, SD = 7.00, n = 54 female (88.5%)). To control for potential practice effects of repeated assessments during the EMA phase, participants were randomly assigned to a control (n = 30) and an interoception (n = 31) group. The latter was assessed for interoceptive accuracy, awareness and sensibility. Before and after the EMA phase, all participants were assessed for interoception in the laboratory. Results: Multilevel analyses revealed significant fluctuations for all three interoceptive facets, around 50% of variance was due to within-person variability. There were only practice effects for the subscale “Attention Regulation”, measuring interoceptive sensibility. Conclusion: The facets of interoception can be assessed in an EMA-setting. Repeated interoceptive assessments do not necessarily lead to an improvement of participants’ interoceptive abilities. It could be shown that all interoceptive facets fluctuate, which should be considered in future research.